EXPLORING THE RELATIONSHIP BETWEEN ACCOUNTING AND STATISTICS - BEBESELEA, Mihaela; PATACHE, Laura (Annals of Spiru Haret University. Economic Series, 2019)
This article highlights the connection between accounting and statistics. There is a historical connection between these quantitative methods of analysis; taking into account the fact that accounting data on property and wealth were requested in census of the great ancient civilizations. Both statistical and accounting data-setting systems provide a framework to identify, to record, to classify and summarize economic activities of entities. Starting from this point of view, we have tried to understand what kind of connection exists between accounting and statistics in the current historical stage of a conform accounting: is it a univocal relationship (accounting serves to statistics or statistics serves accounting) or is it a bi-univocal relationship of reciprocity? In order to find the answer to this question we considered necessary a theoretical approach to this issue, followed by an applied one.